2013
DOI: 10.2166/washdev.2013.050
|View full text |Cite
|
Sign up to set email alerts
|

In-home performance and variability of biosand filters treating turbid surface and rain water in rural Kenya

Abstract: Thirty low-income Kenyan households using turbid river and relatively cleaner rain water participated in a 6 month in-home Biosand filter (BSF) performance study comprised of surveys and monthly monitoring of BSF influent and effluent water for turbidity and fecal coliforms (FC). River–river (influent–effluent) sample pairs (n = 155; 90% of observations) resulted in average BSF instantaneous FC and turbidity removals of 1.41 log10 (96.1%) and 32.5%, respectively. Cumulative distributions of influent and efflue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…In comparison, another study reported that while microbial loading in the feed water only marginally affected the removal of E. coli and coliform bacteria, a loading of 10 6 MPN/L resulted in an 85% removal rate for both [17]. A Kenyan study of 30 households using inhome BSFs reported lower level of effluent fecal coliform in homes (a) that used rainwater only, (b) where children aged 6 to 10 did not collect the filtered water, or (c) that housed fewer family members [65]. The last factor was likely due to the over-use of the filters in homes with larger families, essentially decreasing the HRT, whereas the first factor was directly related to the influent water quality.…”
Section: Source Water Qualitymentioning
confidence: 99%
See 1 more Smart Citation
“…In comparison, another study reported that while microbial loading in the feed water only marginally affected the removal of E. coli and coliform bacteria, a loading of 10 6 MPN/L resulted in an 85% removal rate for both [17]. A Kenyan study of 30 households using inhome BSFs reported lower level of effluent fecal coliform in homes (a) that used rainwater only, (b) where children aged 6 to 10 did not collect the filtered water, or (c) that housed fewer family members [65]. The last factor was likely due to the over-use of the filters in homes with larger families, essentially decreasing the HRT, whereas the first factor was directly related to the influent water quality.…”
Section: Source Water Qualitymentioning
confidence: 99%
“…A randomized controlled trial in rural communities in Tamale, Ghana, reported a 67% geometric mean reduction in turbidity using biosand filters [73]. A six-month study involving 30 Kenyan households each using in-home biosand filters reported a 32% reduction in turbidity [65]. The wide variation in the removal of turbidity is associated with filter characteristics (including media characteristics); operating conditions (including HRT); and, most notably, source water quality, including the specific type of particles that are responsible for the turbidity.…”
Section: Turbiditymentioning
confidence: 99%
“…The cleaning methods most often used were superficial agitation (< 1 cm) and 5 cm stirring (Table S1 -supplementary material). Some studies also carried out maintenance by removing 5 cm of the filtration media (Singer et al, 2017) and by the wet harrowing method (Jenkins et al, 2011;McKenzie et al, 2013;Tiwari et al, 2009). Singer et al (2017) compared three cleaning methods for I-HSSF media: surface agitation (< 1 cm), 5 cm stirring, and 5 cm replacement.…”
Section: Maintenancementioning
confidence: 99%
“…Hydraulic loading rate, defined as the ratio of volumetric flow rate and the filtration cross-sectional area has been reported to have varying degrees of improvement on bacteria efficiencies 6,7,10,21 . It is hypothesized that a slower hydraulic loading rate leads to increased contact time between the bacteria and the surface of the sand grain and the biolayer.…”
Section: Figure 2 a Cawst Specified Diffuser Box (With 1/8" Hole And mentioning
confidence: 99%